2015
DOI: 10.1007/s00198-015-3212-0
|View full text |Cite|
|
Sign up to set email alerts
|

The utility of lumbar spine trabecular bone score and femoral neck bone mineral density for identifying asymptomatic vertebral fractures in well-compensated type 2 diabetic patients

Abstract: TBS and FN-BMD below certain cutoffs may be useful for identifying VFx in well-compensated T2D patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
1
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(38 citation statements)
references
References 33 publications
0
31
1
6
Order By: Relevance
“…The TBS is significantly lower in T2D patients than in normal individuals and is indicative of old or new fractures . It is more accurate than BMD in predicting the risk of fractures in postmenopausal T2D patients and is more significantly correlated with bone strength . The TBS is more valuable for predicting fracture risk when combined with BMD.…”
Section: Bone Quality Assessment In Patients With Diabetesmentioning
confidence: 97%
See 1 more Smart Citation
“…The TBS is significantly lower in T2D patients than in normal individuals and is indicative of old or new fractures . It is more accurate than BMD in predicting the risk of fractures in postmenopausal T2D patients and is more significantly correlated with bone strength . The TBS is more valuable for predicting fracture risk when combined with BMD.…”
Section: Bone Quality Assessment In Patients With Diabetesmentioning
confidence: 97%
“…61 It is more accurate than BMD in predicting the risk of fractures in postmenopausal T2D patients and is more significantly correlated with bone strength. 62,63 The TBS is more valuable for predicting fracture risk when combined with BMD. Results from Chinese women revealed that TBS in combination with BMD is better correlated with vertebral fracture in T2D than BMD alone.…”
Section: Trabecular Bone Scorementioning
confidence: 99%
“…In the US about 25% of citizens over 65 years old have type 2 diabetes mellitus T2DM 26 .The mortality following a hip fracture of a diabetic person has been shown to increase five to eight times fold for the first 3 months after diagnosis and remain elevated for 5 years after 26 .The risk for a hip fracture among elderlies with T2DM is 40-70% higher compared with normoglycemic individuals in the same age group 27 . Hyperglycemia decreases secretion of osteocalcin from osteoblasts and adiponectin from fat cells 28 . Type 2 Diabetes Mellitus (T2DM) increases osteoclastogenesis due to low osteocalcin secretion and restricts proliferation, differentiation and mineralization of osteoblastic cells due to low concentration of adiponectin in blood, leading in bone loss 28 .…”
Section: The Impact Of Type 2 Diabetes Mellitus On Hip Fracture Riskmentioning
confidence: 99%
“…Hyperglycemia decreases secretion of osteocalcin from osteoblasts and adiponectin from fat cells 28 . Type 2 Diabetes Mellitus (T2DM) increases osteoclastogenesis due to low osteocalcin secretion and restricts proliferation, differentiation and mineralization of osteoblastic cells due to low concentration of adiponectin in blood, leading in bone loss 28 . The altered quality and strength of bones in patients with T2DM increase the hip fracture risk but BMD is minimally affected in many cases 26 .…”
Section: The Impact Of Type 2 Diabetes Mellitus On Hip Fracture Riskmentioning
confidence: 99%
“…Однако до настоящего времени не получено достаточного количества данных о роли ТКИ при диагностике остеопороза при СД2. В одной из работ было показано, что использование ТКИ у больных СД2 с хорошей компенсацией заболевания может позволить определить наличие компрессионных переломов позвонков [14]. Применение ТКИ у больных с пограничными значениями 10-летней вероятности переломов по FRAX может позволить определить необходимость начала терапии.…”
Section: цельunclassified